2023
DOI: 10.1021/acs.joc.3c00214
|View full text |Cite
|
Sign up to set email alerts
|

Three-Component Electrochemical Aminoselenation of 1,3-Dienes

Abstract: Azoles and organoselenium compounds are pharmacologically important scaffolds in medicinal chemistry and natural products. We developed an efficient regioselective electrochemical aminoselenation reaction of 1,3-dienes, azoles, and diselenide derivatives to access selenium-containing allylazoles skeletons. This protocol is more economical and environmentally friendly and features a broad substrate scope; pyrazole, triazole, and tetrazolium were all tolerated under the standard conditions, which could be applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The result of the control experiments indicated that both organoselenonium cation and organoselenyl radical could exist in the mechanism. [202] A three-component reaction of alkenes with sulfonimides and diselenides induced by visible light gave the β-amino organylselenides 144 in good yields with excellent functional group compatibility (Scheme 137). The improvement of this methodology includes the absence of additives, photocatalysts, the use of natural sunlight, and the functionalization of biomolecules with styrene.…”
Section: Diorganyl Diselenides Promoting Reduction Of Alkenesmentioning
confidence: 99%
“…The result of the control experiments indicated that both organoselenonium cation and organoselenyl radical could exist in the mechanism. [202] A three-component reaction of alkenes with sulfonimides and diselenides induced by visible light gave the β-amino organylselenides 144 in good yields with excellent functional group compatibility (Scheme 137). The improvement of this methodology includes the absence of additives, photocatalysts, the use of natural sunlight, and the functionalization of biomolecules with styrene.…”
Section: Diorganyl Diselenides Promoting Reduction Of Alkenesmentioning
confidence: 99%
“…Similarly, Meng and co-workers achieved the electrochemical intermolecular three-component transformation of 1,3-dienes, azoles and diselenides (Scheme 5). 26 The best result was obtained with a yield of 78% in the presence of NaHCO 3 as the base, LiClO 4 as the electrolyte, a CH 3 CN/HFIP mixture as the solvent, reticulated vitreous carbon (RVC) as the anode and stainless steel (SS) as the cathode, operated at 10 mA current in an undivided cell system. The substrate potential of the optimized reaction conditions was further examined for differently substituted 1-aryl-1,3-butadiene, azoles and diselenides, which were tolerated in moderate to good yields with high regioselectivity (…”
Section: Intermolecular Selenofunctionalizationmentioning
confidence: 99%
“…Although the construction of new carbon–carbon bonds through functionalization of the diene has been intensively investigated, selective installation of two heteroatoms onto 1,3-dienes remains a challenge. Over the past few decades, selective diamination, aminothiolation, aminooxygenation, aminofluorination, amidoazidation, aminoisothiocyanation, and other difunctionalization methods of 1,3-dienes have been developed. Despite significant progress, it is surprising to observe that selective concurrent installation of two amino and phosphorus heteroatoms onto 1,3-dienes has not yet been explored.…”
mentioning
confidence: 99%